تقييم تأثير طرق الزراعة المختلفة على إنتاجية القمح الطري (Triticum aestivum L.) تحت نظام الري التكميلي في المنطقة الغربية من ليبيا - فرج على جبيل; مختار عمر عقوب; عبدالرحيم محمد بن سعيدان; حسن تنتون; أبولبيدة المجدوب (Aljameai, 2026)
المستخلص:أجريت هذه الدراسة خلال الموسم الزراعي (2024 - 2025) بمحطة مصراتة للبحوث الزراعية التابعة لمركز البحوث الزراعية والحيوانية، وبهدف دراسة تأثير طرق الزراعة على إنتاجية القمح الطري Triticum aestivum L.)) صنف بحوث 210 بنظام الري التكميلي في المنطقة الغربية من ليبيا. استخدم تصميم القطاعات العشوائية الكاملة (RCBD)بثلاث مكررات، شملت المعاملات ثلاث طرق للزراعة هي. الزراعة باستخدام آلة ا لبذار، الزراعة بالناثرة القمعية مع التغطية بالمحراث الحفار (سكة رجل البطة)، والزراعة التقليدية بالنثر اليدوي مع التغطية بالمحراث الدوراني (الشاهد). بلغت مساحة القطعة التجريبية الواحدة 1200 م². تضمنت الدراسة جمع البيانات وقياس صفات النمو ومكونات المحصول والإنتاجية. وأظهرت النتائج عدم وجود فروق معنوية بين طرق الزراعة في عدد النباتات، ارتفاع النبات، عدد السنابل، طول السنبلة، عدد حبوب السنبلة، وزن ألف حبة، الوزن النوعي، الإنتاج الحيوي، إنتاجية الحبوب، إنتاجية التبن، رغم وجود فروق عددية بين المتوسطات. سجلت فروق معنوية في وزن حبوب السنبلة حيث تفوقت معاملة الزراعة باستخدام آلة البذار بتحقيق اعلى متوسط (1.91 جم)، وتشير النتائج الى ان الزراعة باستخدام آلة البذار تعد الأكثر كفاءة من الناحية الإنتاجية تحت ظروف منطقة الدراسة. لذلك نوصي باعتمادها في زراعة محصول القمح الطري لتحسين إنتاجية الحبوب. AbstractThis study was conducted during the 2024–2025 growing season at the Misrata Agricultural Research Station affiliated with the Agricultural and Animal Research Center, with the aim of evaluating the effect of sowing methods on the productivity of bread wheat (Triticum aestivum L.), cultivar Buhuth 210, under a supplemental irrigation system in the western region of Libya. A Randomized Complete Block Design (RCBD) with three replications was used. The experiment included three sowing methods: sowing using a seed drill, sowing with a funnel broadcaster followed by covering using a chisel plow (duck-foot share), and the conventional manual broadcasting method followed by covering using a rotary tiller (control treatment). The area of each experimental plot was 1200 m². Data were collected to evaluate growth traits, yield components, and productivity parameters. The results showed no significant differences among sowing methods in plant population, plant height, number of spikes, spike length, number of grains per spike, thousand-grain weight, test weight, biological yield, grain yield, and straw yield, although numerical differences among treatment means were observed. Significant differences were detected in spike grain weight, where the seed drill treatment recorded the highest mean value (1.91 g). The results indicate that sowing using a seed drill was the most efficient method in terms of productivity under the environmental conditions of the study area. Therefore, the adoption of seed drill sowing is recommended for bread wheat cultivation to improve grain productivity.